2019
DOI: 10.1155/2019/3616284
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity of Beef Calves in Free-Range Farms in Alentejo, Portugal—A Preliminary Study

Abstract: Extensive cow-calf beef cattle farms play a significant role in Portuguese livestock production, but records of important production variables, such as calf mortality, are scarce. To assess herd-level calf mortality and its potential economic impact, farmers from the Alentejo region were asked to fill a questionnaire regarding herd size, feeding and reproductive management practices, calf mortality (from birth to weaning), and detection of the main morbidity causes, as well as of sudden, unexplained deaths dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The hazard for mortality was higher in relatively large-sized dairy herds when compared to smaller herd sizes. This finding was supported by Santos et al ( 52 ), who reported that herd size has a predictive value on calf mortality from birth to weaning.…”
Section: Discussionsupporting
confidence: 73%
“…The hazard for mortality was higher in relatively large-sized dairy herds when compared to smaller herd sizes. This finding was supported by Santos et al ( 52 ), who reported that herd size has a predictive value on calf mortality from birth to weaning.…”
Section: Discussionsupporting
confidence: 73%
“…Raboisson et al (2016) estimated that the costs of low colostrum intake causing increased calf mortality was 80 EUR per calf in beef herds. Furthermore, Santos et al (2019) concluded that calf diarrhoea, respiratory disease, and sudden, unexplained deaths are common causes of calf mortality and have a large impact on the farm economy. Several other studies have also confirmed that calf survival has high economic importance (Koots and Gibson, 1998;Phocas et al, 1998;Wolfová et al, 2005a).…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…This amplifies no improvement within the past decade and a half. South Africa is reporting annually higher losses than countries such as Brazil 4.1% and Portugal 5.7% [ 45 , 46 ]. Records in these countries may be influenced by openness to adoption of developmental programs such as the Welfare Assessment Protocol applied in New Zealand and Namibia.…”
Section: Discussionmentioning
confidence: 99%